Non-compliance in the Distribution and Management of Zakat: An Islamic Legal Perspective - Sucipto, Sucipto; Adawiah, Rabiatul; Subhan, Muhammad; Siregar, Erwin Saputra (Nurani, 2025)
This study investigates the operations of unlicensed zakat institutions, with particular attention to problems such as the absence of accountable reporting, the misallocation of zakat funds away from legitimate beneficiaries (mustahik), and the emergence of fraudulent claimants (jockeys). This study adopts a qualitative approach with an exploratory design to understand the phenomenon of zakat institutions' non-compliance with sharia principles, particularly in the context of legality and governance. The findings reveal structural and operational shortcomings contributing to non-compliance and misalignment with existing policies. The study advocates a shift in research orientation from predominantly ritualistic dimensions toward justice-oriented and religiously humanist policy frameworks. It emphasizes the need to prioritize equitable distribution over technocratic classifications of mustahik while resisting communal or political domination, particularly in political networks. The politicization of zakat, particularly in the context of the 2024 election, has undermined its spiritual and social objectives. Ensuring compliance with sharī‘ah principles is therefore crucial for establishing legal certainty, strengthening public trust, and enabling zakat to realize its full potential as a transformative instrument for community empowerment in Indonesia.